2011
DOI: 10.1103/physrevd.83.123506
|View full text |Cite
|
Sign up to set email alerts
|

Is there further evidence for spatial variation of fundamental constants?

Abstract: The detection of a spatial variation of the fine-structure constant, α, based on study of quasar absorption systems has recently been reported [1]. The physics that causes this α-variation should have other observable manifestations, and this motivates us to look for complementary astrophysical effects. In this paper we propose a method to test whether spatial variation of fundamental constants existed during the epoch of big bang nucleosynthesis. Using existing measurements of primordial deuterium abundance w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 46 publications
(81 reference statements)
4
49
2
Order By: Relevance
“…Other analyses have confirmed these results [3,4], although the inclusion of more recent measurements reduces the allowed amplitude by about twenty percent [5], to a maximum of about 8 parts per million (with no significant changes to the preferred direction). Although it is clear that some systematic effects are present in the archival data [6], it is presently unclear if they could explain the above results [7,8].…”
Section: Introductionsupporting
confidence: 56%
“…Other analyses have confirmed these results [3,4], although the inclusion of more recent measurements reduces the allowed amplitude by about twenty percent [5], to a maximum of about 8 parts per million (with no significant changes to the preferred direction). Although it is clear that some systematic effects are present in the archival data [6], it is presently unclear if they could explain the above results [7,8].…”
Section: Introductionsupporting
confidence: 56%
“…So far, none are found which are likely to emulate the apparent cosmological dipole in α we detect. Consistency with other astronomical data is discussed in [14]. Consistency with laboratory, meteorite, and Oklo natural reactor is discussed in [15].…”
Section: Fig 2 ∆α/α For the Combined Keck And Vlt Data Vs Anglementioning
confidence: 99%
“…King et al (2012) have re-analyzed the VLT and Keck Observatory data and found a non-null spatial variation of α, and that the dipole model is preferred over the monopole model. Berengut et al (2011) have demonstrated that it is possible to set constraints on the spatial variation of the fine structure constant using Big Bang nucleosynthesis (BBN) primordial abundances, though the existing data on it do not support the dipole interpretation. A geophysical analysis to test the spatial variation of α was performed by Berengut & Flambaum (2012).…”
Section: Introductionmentioning
confidence: 99%